CCNA 200-301. Official cert guide. Volume 1 - Odom, Wendell (Official cert guide, 2024)
"CCNA 200-301 Official Cert Guide, Volume 1 from Cisco Press enables you to succeed on the exam the first time and is the only self-study resource approved by Cisco. Best-selling author Wendell Odom shares preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills. This official study guide helps you master all the topics on the CCNA 200-301 exam, including Networking fundamentals Implementing Ethernet LANs Implementing VLANs and STP IPv4 addressing and subnetting IPv4 routing Implementing OSPF"--